Conduction velocity and refractory period of single motor nerve fibres in antecedent poliomyelitis. Issue 4 (April 1987) - Borg, K; Borg, J
Abstract : The axonal conduction velocity and the axonal refractory period were determined using electromyographic techniques for 60 single motor units in 11 patients with antecedent poliomyelitis. The results were compared with previous observations in healthy subjects as well as subjects with motor neuron disease. In antecedent poliomyelitis there was a reduced proportion of nerve fibres with low conduction velocity as compared with the findings in healthy subjects. The mean value of the axonal conduction velocities in antecedent poliomyelitis (42.4 +/- 3.7 m/s, M +/- SD) was significantly higher (p less than 0.01) while in motor neuron disease the corresponding value (35.2 +/- 7.8 m/s) was significantly lower (p less than 0.005) than in healthy subjects (39.8 +/- 4.9 m/s). In antecedent poliomyelitis the conduction velocity and refractory period were related as in healthy subjects while abnormally long refractory periods were observed in motor neuron disease.